Case-control study of risk factors for Penicillium marneffei infection in human immunodeficiency virus-infected patients in northern Thailand - Chariyalertsak S. (2014)
A case-control study was done in Chiang Mai, Thailand, comparing risk-related behavior and exposures in 80 incident cases of disseminated Penicillium marneffei infection in patients with AIDS and 160 control patients with AIDS who did not have P. marneffei infection. All subjects were admitted to Chiang Mai University Hospital between December 1993 and October 1995. Cases were younger than controls (16-30 years vs. > 30 years of age; odds ratio [OR] = 2.22; 95% CI, 1.22-4.07). Patients with a recent history of occupational or other exposure to soil, especially during the rainy season (May to October), were more likely to present with P. marneffei infection (OR = 1.91; 95% CI, 1.04-3.52). History of exposure to or consumption of bamboo rats, the only known nonhuman hosts of P. marneffei, was not a risk factor for infection. Our data suggest that recent exposure to a potential environmental reservoir of organisms in the soil may be associated with disseminated P. marneffei infections among patients with AIDS in Northern Thailand.